Lymph node, peritoneal and bone marrow micrometastases in gastric cancer: Their clinical significance - Griniatsos, John (Baishideng Publishing Group Co., Limited, 2012)
The 7th TNM classification clearly states that micrometastases detected by morphological techniques (HE stain and immunohistochemistry) should always be reported and calculated in the staging of the disease (pN1mi or M1), while patients in whom micrometastases are detected by non-morphological techniques (e.g., flow cytometry, reverse-transcriptase polymerase chain reaction) should still be classified as N0 or M0. In gastric cancer patients, micrometastases have been detected in lymph nodes, the peritoneal cavity and bone marrow. However, the clinical implications and/or their prognostic significance are still a matter of debate. Current literature suggests that lymph node micrometastases should be encountered for the loco-regional staging of the disease, while skip lymph node micrometastases should also be encountered in the total number of infiltrated lymph nodes. Peritoneal fluid cytology examination should be obligatorily performed in pT3 or pT4 tumors. A positive cytology classifies gastric cancer patients as stage IV. Although a curative resection is not precluded, these patients face an overall dismal prognosis. Whether patients with a positive cytology should be treated similarly to patients with macroscopic peritoneal recurrence should be evaluated further. Gastric cancer cells are detected with high incidence in the bone marrow. However, the published results make comparison of data between groups almost impossible due to severe methodological problems. If these methodological problems are overcome in the future, specific target therapies may be designed for specific groups of patients.